Occurrence of syphilis in the young patient who coinfected with human immunodeficiency virus: A dangerous combination case report - Mayur Wanjari; Sampada Late; Tejaswee Lohakare (Journal of Family Medicine and Primary Care, 2022)
Several complications can occur if syphilis is not treated at an early stage. Several developing countries recently remerged the high cases of syphilis with human immunodeficiency. We reported the case of 26-years-old male infected with syphilis with the human immunodeficiency virus (HIV). The patient sole and palm contain lesions. In our patient, HIV was diagnosed 2 years earlier in the prophylactic studies but had not taken any medical management. The penicillin G was taken to the patient to reverse the lesions, and it was successfully treated. The patient also was on antiretroviral therapy for the improvement in immune status. This case highlighted the importance of early management of any inflammatory cutaneous disease with HIV infections that can prevent the severity of the disease condition.